Efficacy of fungicides, bioagents and organic amendments against rhizome rot diseases of ginger - MINI SANKAR, SUJATHA, V., ANJALY VARGHESE and FRIDIN DAVIS, RESHMY VIJAYARAGHAVAN, SALLY K. MATHEW (Indian Phytopathology, 2016)
Field experiments cum multi locational trials wereconducted for two consecutive years at Wayanad, Thrissur and Palakkad district both in research stations as well as in farmer’s field, to study the effect of fungicides, biocontrol agents and other organic amendments against rhizome rot diseases of ginger. A total of 14 treatments were laid out in the first year which was reduced to 10 in the second year based on the efficacy of the treatments. Rhizome rot incidence was observed in all locations caused by the pathogens viz., Pythium aphanidermatum and Rhizoctonia solani. Lowest PDI was observed in treatment T2(carbendazim+mancozeb) followed by the combination treatment of bleaching powder + lime (T8), T4(mancozeb+B.P+ lime) and T5 (Pf+cowdung slurry supernatant). Considering the 3 parameters, per cent germination, PDI and yield, combination of carbendazim+mancozeb(0.2%) was the most effective treatment. Among the treatments recommended for ginger production by organic methods, application of B.P (15g) + lime (250g) per 3m2bed and drenching with P.f (2%) + cowdung slurry supernatant (2%) are found to be promising.